The original Olympics - Ross, Stewart (New York : Bedrick, 1999)
Discusses the history, traditions, and competitive events connected with the Olympic games held in ancient Greece.
Includes bibliographical references and index.
2-6.
Keywords: Olympic games; Ancient history